A human cadaveric workshop: One solution to competence in the face of rarity. (13th May 2016) - Ferguson, Ian MC; Shareef, Mohammed Z; Burns, Brian; Reid, Cliff
Abstract: Competent performance of cricothyroidotomy, lateral canthotomy and resuscitative thoracostomy is an expected standard for Australasian emergency physicians, but infrequent exposure to these procedures could impair physician confidence, reducing the likelihood of their execution in a critical timeframe. Training to perform these procedures is a recognised challenge for non‐surgeons, and cadaver‐based training is one method of addressing this need. We describe a 1 day cadaver‐based workshop for emergency medicine doctors and briefly report on its impact on physician confidence. This workshop appeared effective in increasing the confidence of emergency medicine physicians to carry out rarely performed life and sight‐saving procedures and also provides an opportunity for senior clinicians to increase compliance with continuing profession development schemes.